Extraction of Basil Leaves Essential Oil using Microwave Assisted Hydrodistillation Method: Physical Characterization and Antibacterial Activity - Putri, Ditta Kharisma Yolanda; Putri, Salsabila Ananda; Nugraha, Briantara Agung; Fachri, Boy Arief; Palupi, Bekti (CHEESA: Chemical Engineering Research Articles, 2023)
Basil oil can be obtained from basil leaves by non-extraction methods, namely Microwave Assisted Hydrodistillation (MAHD). Therefore, this research aims to determine the yield percentage, essential oil composition by GC-MS, physical characteristics, and antibacterial activity of basil essential oil. The highest yield of 0.3076% was obtained at the optimum condition, which included a microwave power of 300 W, a mass-to-volume solvent ratio (F/S) of 0.75 g/mL, a raw material size of ± 1.75 cm, and an extraction time of 90 min. The results of the analysis of variance showed that all process parameters used had a significant effect on the yield obtained. Basil oil exhibited a larger inhibition zone against Escherichia coli bacteria (16.38 mm) which tended to be stronger than Staphylococcus aureus (5.95 mm) and was classified as moderate. The main components contained in the basil oil were E-Citral (46.79%) and Z-Citral (38.17%). The physical characteristic test showed that the basil oil was soluble in 96% ethanol after a ratio of 1:9, with 1 ml of basil oil compared to 9 ml of ethanol. The density of basil oil at 0.961 g/mL also complied with the standard value according to the Essential Oil Association (EOA) of Ocimum basilicum Essential Oil. These results showed revealed that the parameter analyzed using oil yields at operating conditions produced the most optimum yield value.